ADOLESCENT DEMENTIA CAREGIVERS: PERCEPTIONS, CHALLENGES AND OPPORTUNITIES. (11th November 2018) - Perion, J; Ames, A; Steiner, V
Abstract: The National Alzheimer's Association estimates that 250, 000 youths under the age of 18 help support a family member with dementia, but few studies exist to shed light on the tasks performed, or whether caregiving influences psychological well-being. Adolescents age 12–17 participated in focus groups as part of an exploratory study to understand how they experience caregiving roles. Five males and six females living in northwest Ohio with an average age of 15 were recruited. Four participants were African-American, seven were White; one identified as Hispanic/Latino. All but one were attending school, and most reported their health as excellent or very good. Caregiving was provided for three grandmothers, five grandfathers, two great-grandfathers, a great-grandmother, and an uncle. A qualitative thematic analysis of the data revealed themes related to caregiving tasks performed, training and support needs, perceptions of family obligation, and psychological well-being. Caregiving duties ranged from companionship to medical care. Adolescents as young as 12 managed medications and a number of the youths performed tasks healthcare workers often assist with, such as bathing and toileting. When present, training and support was primarily informal and self-initiated. The participants expressed an appreciation for the importance of family support, did not think the caregiving tasks interfered with other social aspects of their lives, and most held positive views of their caregiving experiences. The findings of this study provide new insight into the experience of dementia caregiving that can be used to develop supportive and enriching programs aimed at increasing the wellbeing of caregiving youths.